7(m+7)=40-2m

Simple and best practice solution for 7(m+7)=40-2m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(m+7)=40-2m equation:


Simplifying
7(m + 7) = 40 + -2m

Reorder the terms:
7(7 + m) = 40 + -2m
(7 * 7 + m * 7) = 40 + -2m
(49 + 7m) = 40 + -2m

Solving
49 + 7m = 40 + -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
49 + 7m + 2m = 40 + -2m + 2m

Combine like terms: 7m + 2m = 9m
49 + 9m = 40 + -2m + 2m

Combine like terms: -2m + 2m = 0
49 + 9m = 40 + 0
49 + 9m = 40

Add '-49' to each side of the equation.
49 + -49 + 9m = 40 + -49

Combine like terms: 49 + -49 = 0
0 + 9m = 40 + -49
9m = 40 + -49

Combine like terms: 40 + -49 = -9
9m = -9

Divide each side by '9'.
m = -1

Simplifying
m = -1

See similar equations:

| 9y+9=15 | | X+x1/2x+1/2x=360 | | (6+2a)=1/2(4a-6) | | 4w-3w+2w+8=-16 | | 5x+6(x+10)=170 | | 15=2a-5a | | n/6=n/2-7/3 | | -4p+4=12 | | 21=-x+4x+9 | | (9*6)+-4= | | 6x-5x=4 | | -9(n-12)=3(1+8n)-12n | | x=40/(x+6) | | y=2x^3-3x^2-36x | | (4/a-2)+(5/a+2)=(5/a^2-4) | | b-5/4=b+2/3 | | -13=3-2x-4 | | -8x(.09)x(-.5)= | | -110=-5x | | 6r-7(4r+2)=28-8r | | 10+5x-7=8x+8-3x | | 3x^3y+3x^2-9x^2y=0 | | 4.50+0.05x=0.2x | | 8n+2=-2n-8 | | p-38=47/5(h-7) | | -(2x-7)=7-2x | | 1-6n-1=18 | | 4y+2+6y-50=180 | | 3(-2x+1)-5=10 | | -2p+3=p+9 | | .5y-3=2y+12 | | s+6=4 |

Equations solver categories